A study on the evolution of the contact angle of small punch creep test of Ductile materials - Cacciapuoti, B.; Sun, Wei; McCartney, D.G. (Elsevier, 2016)
The work discussed in the present paper reports a novel investigation of the applicability of Chakrabarty's theory, for membrane stretching of a circular blank over a rigid punch, to small punch creep test (SPCT). The Chakrabarty solution was compared with corresponding results obtained by numerical finite element (FE) analyses and experimental tests. The Liu and Murakami creep damage model was used in the FE analyses. The aim of the work is also to improve the understanding of the mechanism governing the deformation and the failure of the specimen and to verify the range of applicability of the CEN Code of Practice CWA 15627, which is based on Chakrabarty's theory. The effects of various parameters, such as the initial thickness of the specimen, the radius of the punch, the load magnitude, the friction coefficient and different plasticity constitutive models, on the variation of the contact angle, θ0, and the central displacement of the punch, Δ, were identified and correlated by fitting equations. The variation of θ0 with Δ, obtained from Chakrabarty's solution was compared with that obtained by FE analyses of the SPCT. When the initial thickness of the specimen increased and the radius of the punch decreased, the FE results, in terms of the variation of θ0 versus Δ, showed to differ from Chakrabarty's solution, therefore new ranges of applicability of the CEN Code of Practice CWA 15627 were determined.